Simultaneous removal of SO2 and NO by CO reduction over prevulcanized Fe2O3/AC catalysts. (21st February 2019) - Song, Yongji; Wang, Ting; Cheng, Liang; Li, Cuiqing; Wang, Hong; Wang, Xincheng
Abstract: Low‐cost Fe2 O3 modified activated carbon catalysts have been prepared by a facile incipient‐wetness impregnation method and used for the low‐temperature simultaneous catalytic reduction of SO2 and NO by CO. The effect of CO, NO, and SO2 was studied experimentally by transient response method. Removal efficiencies of 95 % for NO and 100 % for SO2 were obtained, respectively, for the optimum catalyst, in which the amount of Fe2 O3 was 10 wt%. It was found that the catalyst was robust enough under SO2 and NO circumstances; moreover, the prevulcanization of Fe atoms was found to be essential for high efficiency. The reaction mechanism of the simultaneous desulphurization and denitrification reactions of Fe2 O3 /AC was proposed to follow both redox and COS mechanisms. These results make activated carbon supported Fe2 O3 highly promising for the simultaneous abatement of SO2 and NO emissions generated during the combustion processes. Abstract : Prevulcanized Fe2 O3 ‐based activated carbon was proven to be an efficient catalyst for simultaneous removal of SO2 and NO by CO reduction, following both redox and COS mechanisms.